Nitrate Reduction by Roots of Soybean (Glycine max [L.] Merr.) Seedlings - Crafts-Brandner, Steven J. (1982)
Studies were conducted with 9 to 12 day-old soybean (Glycine max [L.] Merr. cv. Williams) seedlings to determine the contribution of roots to whole plant NO(3)(−) reduction. Using an in vivo -NO(3)(−) nitrate reductase (NR) assay (no exogenous NO(3)(−) added to incubation medium) developed for roots, the roots accounted for approximately 30% of whole plant nitrate reductase activity (NRA) of plants grown on 15 mm NO(3)(−). Nitrogen analyses of xylem exudate showed that 53 to 66% of the total-N was as reduced-N, depending on the time of day of exudate collection. These observations supported enzyme data that suggested roots were contributing significantly to whole plant NO(3)(−) reduction. In short-term feeding studies using (15)N-NO(3)(−) significant and increasing atom percent (15)N excess was found in the reduced-N fraction of xylem exudate at 1.5 and 3 hours after feeding, respectively, which verified that roots were capable of reducing NO(3)(−). Estimated reduced-N accumulation by plants based on in vivo -NO(3)(−) NR assays of all plant parts substantially over-estimated actual reduced-N accumulation by the plants. Thus, the in vivo NR assay cannot be used to accurately estimate reduced-N accumulation but still serves as a useful assay for relative differences in treatment conditions.